Waste processing without causing public health problems with black soldier fly bioconversion - Zahra, Afifah; Herdiansyah, Herdis; Utomo, Suyud Warno; Nuraeni, Nuraeni (International Journal of Public Health Science (IJPHS), 2024)
Bioconversion of black soldier fly (BSF) larvae is a method of processing organic waste that is environmentally friendly and has no impact on public health. This research aims to analyze the influence of the type of waste as a feed formulation on the effectiveness of organic waste processing with bioconversion of black soldier fly larvae. The research was conducted in Tubunan Village, Jepara Regency, the district with the second lowest waste processing in Central Java on 108 families. The initial procedure for this experimental research was carried out by sorting the types of waste (community waste, fish slaughter waste, and a mixture of both). Each type of waste is then given 1.5 grams of larvae/kg of waste. The larvae will be harvested after 20 days and weighed to record data on the increase in biomass and waste left behind. The collected data was then analyzed using SPSS through ANOVA and Kruskal Wallis tests. The results showed that the nutritional formulation of the feed had a significant effect on total larval biomass (p=0.0005) but had no significant effect on the waste reduction index (p=0.651) and feed conversion efficiency (p=0.180). In this study, processing organic waste with bioconversion of black soldier fly larvae reduced waste piles significantly (p=0.008). Thus, bioconversion waste processing using BSF can solve the waste problem at the research location. These findings can be considered in planning effective and efficient waste processing.